Kuliah Kerja Nyata: Pengabdian Kepada Masyarakat Melalui Kegiatan Penguatan Ideologi Pancasila - Agil Surya Fajar; Afifah Nurulita Sari (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The aim of this service is to improve and strengthen the values and ideology of Pancasila for all community members in Teter Village, Simo District, Boyolali Regency. The problem behind this activity is that students receive a mandatory campus program, namely Real Work Lectures (KKN) as Pancasila movement students located in Teter Village, Simo District, Boyolali Regency. There are various customs and cultures inherent in the Teter Village community, therefore the Pancasila movement students intend to carry out several work programs aimed at all residents of the Teter Village community. By providing socialization of Pancasila values and creative content training on the Pancasila theme. The way to implement Real Work Lecture activities refers to the following systematics: forming a team, formulating goals, identifying stakeholders, collecting and analyzing needs, determining priorities for solving problems, preparation, implementation, mentoring, review and evaluation, and determining new needs and targets.